A Short and Versatile Approach for the Synthesis of Pyrrolizidinones. Issue 3 (1st February 2022) - Dagoneau, Dylan; Quinodoz, Pierre; Kolleth, Amandine; Bozoflu, Mert; Horoz, Beyza; Catak, Saron; Poisson, Philippe‐Alexandre; Lumbroso, Alexandre; Sulzer‐Mossé, Sarah; De Mesmaeker, Alain
Abstract: Herein we describe a novel 3‐step synthesis of pyrrolizidinone derivatives with good overall yield. This sequence relies on first a [2+2] cycloaddition between a keteniminium salt intermediate, bearing an alkyl chloride side chain, and an alkene partner furnishing the corresponding cyclobutanone after hydrolysis of the resulting cyclobutaniminium. Then ring expansion towards the γ‐lactam using a Beckmann ‐type rearrangement followed by intramolecular SN 2 reaction in the presence of a base triggers the second ring formation of the process. This approach, which is particularly straightforward, allows a broad diversification of pyrrolizidinones by changing the nature of the substituents on the starting alkene and on the keteniminium precursor. Additionally, a computational study was conducted to assess the activation barrier of the SN 2 step on different intermediates as well as the nitrogen pyramidalization of the resulting pyrrolizidinones adducts. Abstract :